Effect of Asphalt Binders Modified with Additives on the Properties of Asphalt Mixtures - Ramírez Castro , Laura (2025)
This study analyzes the changes in the physical properties of asphalt binders resulting from the incorporation of elastomeric and plastomeric modifiers, as well as lime, and how these changes affect the performance of the asphalt mixture.